Genomic mechanisms underlying PARK2 large deletions identified in a cohort of patients with PD. (June 2016) - Morais, Sara; Bastos-Ferreira, Rita; Sequeiros, Jorge; Alonso, Isabel
Abstract : Objectives: To identify the genomic mechanisms that result in PARK2 large gene deletions. Methods: We conducted mutation screening using PCR amplification of PARK2 -coding regions and exon-intron boundaries, followed by sequencing to evaluate a large series of 244 unrelated Portuguese patients with symptoms of Parkinson disease. For the detection of large gene rearrangements, we performed multiplex ligation-dependent probe amplification, followed by long-range PCR and sequencing to map deletion breakpoints. Results: We identified biallelic pathogenic parkin mutations in 40 of the 244 patients. There were 18 different mutations, some of them novel. This study included mapping of 17 deletion breakpoints showing that nonhomologous end joining is the most common mechanism responsible for these gene rearrangements. None of these deletion breakpoints were previously described, and only one was present in 2 unrelated families, indicating that most of the deletions result from independent events. Conclusions: The c.155delA mutation is highly prevalent in the Portuguese population (62.5% of the cases). Large deletions were present in 42.5% of the patients. We present the largest study on the molecular mechanisms that mediate PARK2 deletions in a homogeneous population.